JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF THE MOLINA APPLICATION IN PROVIDING LEGAL CERTAINTY FOR IMMIGRATION PERMITS FOR FOREIGNERS IN INDONESIA (CASE STUDY AT THE BATAM CLASS I SPECIAL IMMIGRATION OFFICE TPI) - Richard Jandres Tarigan; Lagat Parroha Patar Siadari; Sayid Fadhil (RADJA PUBLIKA, 2025)
The development of information technology has driven bureaucratic reform in various sectors of public service, including the field of immigration. One innovation by the Directorate General of Immigration is implementing the Molina application (Residence Permit and Immigration Status Service Module), which aims to simplify the residence permit service process for foreigners in Indonesia. However, the implementation of this application still faces various challenges, both from legal, technical, and social aspects. This study aims to analyze the legal framework and implementation of the Molina application and evaluate the extent to which it can provide legal certainty in residence permit services, particularly at the Special Immigration Office Class I TPI Batam. The research methods used are normative and empirical juridical, emphasizing statutory and sociological (socio-legal) approaches. Data was obtained through literature review and field research through interviews with immigration officers and service users. The analysis was conducted using responsive law theory (Philippe Nonet & Philip Selznick) as the grand theory, legal system theory (Lawrence M. Friedman) as the middle theory, and the theory of legal certainty (Sudikno Mertokusumo) as the applied theory. The results show that, normatively, the Molina application has not yet been fully supported by precise and uniform technical regulations, which have the potential to create legal uncertainty in its implementation. In terms of implementation, the application has improved efficiency but still faces obstacles in technical aspects, human resource readiness, and a legal culture that does not yet provide optimal support. Therefore, it is recommended that the government and relevant agencies update regulations, provide human resource training, and educate the public to realize a digital-based immigration service that is reliable, fair, and sustainable.